Pelaksanaan Pasal 280 Undang-Undang Republik Indonesia Nomor 7 Tahun 2017 tentang Pemilihan Umum: Pelanggaran Kampanye Pemilu 2019 di Kabupaten Blitar - Abdul Hakam Sholahuddin; Anik Iftitah; Uun Dewi Mahmudah (Jurnal Supremasi, 2019)
Potential for Election violations is prone to occur in the campaign stage as a moment for the Election Contestants in the 2019 Election to introduce themselves to the public to be elected. Considering this, the empirical legal research "Implementation of Article 280 of the Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections" with research sites in Blitar Regency becomes urgent to be examined as a reflection of the quality of the implementation of Indonesian Elections in the regions. The discovery of thousands of campaign props in prohibited places in the implementation of the campaign stages in Blitar Regency should be regulated following statutory regulations